Impedance-Matching Range Extension Method for Maximum Power Transfer Tracking in IPT System - Dai, Xin; Li, Xiaofei; Li, Yanling; Hu, Aiguo Patrick (IEEE transactions on power electronics, 2018)
Maximum power transfer is an important index for an inductive power transfer (IPT) system to make full use of its power transfer capability, and such a capability is usually realized by impedance matching. Traditionally, impedance matching is implemented by placing a power electronics converter such as a dc-dc converter at the secondary side of an IPT system. However, the power electronics converter and its operation mode directly affect its impedance-matching range, which is very limited if a traditional power converter only operates at continuous conduction mode (CCM). To extend the impedance-matching range, this paper proposes a novel impedance matching method based on combined CCM and discontinuous conduction mode (DCM) operation of an impedance matching converter. The impedance-matching range is fully analyzed for CCM and DCM operation, respectively, by taking variation of coupling coefficient into consideration. The analysis results show that the impedance-matching range can be extended by more than double that of the traditional impedance matching method. In addition, a maximum power transfer tracking method is developed using the proposed impedance-matching range extension method, and the experimental results have verified the feasibility of the tracking method.